Analysis of the influence of audit characteristics, company characteristics, and audit committe on auditor replacement in companies listed on the Indonesia Stock Exchange - Supriyanto Supriyanto (Jurnal Ekonomi LLDIKTI Wilayah 1 (JUKET), 2022)
This research was conducted with the aim of analyzing the effect of audit characteristics, company characteristics and audit committee on auditor turnover. The sample of companies used in this study were 453 companies listed on the Indonesia Stock Exchange from 2015 to 2019. The audit characteristic classification variables are auditor reputation and audit opinion. The variables for categorizing company characteristics are financial distress, change of management, and leverage. The data obtained were then processed using the SPSS program. The results showed that the auditor's reputation and profitability had a significant effect on auditor switching, while financial difficulties, management changes, audit opinion, audit committee, and leverage had no significant effect on auditor switching